Density threshold‐based acaricide application for the two‐spotted spider mite Tetranychus urticae on cassava: from laboratory to the field. Issue 10 (22nd March 2019) - Chen, Qing; Liang, Xiao; Wu, Chunling; Gao, Jintao; Chen, Qian; Zhang, Zhe
ABSTRACT: BACKGROUD: The red spider mite Tetranychus urticae is known as a worldwide pest in cassava production which can caused serious economic losses. Because no threshold levels are established for T. urticae in cassava cropping, many growers in China are applying excessive chemical applications per cassava cropping period. This is not only expensive, but also results in lower yields because of severe leaf damage and development of resistance. This study aims to develop an immediate threshold level for T. urticae control which could be determined in the laboratory and fit the field application requirements. RESULTS: The mite density of 25 mites/leaf was the threshold which caused significant decrease of photosynthetic pigment contents and protective enzyme activities in cassava leaves in the laboratory. Moreover, 25 mites/leaf was also the threshold density which resulted in significantly lower leaf damage and higher yield levels compared with a higher level of mites/leaf where calendar sprays were used. CONCLUSION: The mite density threshold that brought about significant physiological and biochemical changes in the laboratory basically coincided with the threshold that resulted in significant yield loss in the field. It is therefore concluded that the optimum threshold acaricide spray for T. urticae on cassava is 25 mites/leaf. © 2019 Society of Chemical Industry Abstract : The density of 25 mites/leaf which caused significant physiological changes in the laboratory and yield loss in the field could be used as the acaricide application threshold in cassava mite control.